Evaluation of NPK doses on the production of papaya ‘Caliman 01’ - Albuquerque, Gustavo Henrique; Soares, Ismail; Aquino, Boanerges; Miranda, Fabio; Dutra, Indalécio (Revista Ciência Agronômica, 2019)
The study aimed to evaluate the effect of different NPK doses on the yield components of papaya hybrid ‘Caliman 01’. The experiment was carried at the company WG Fruticultura, located in the Chapada do Apodi region. Five nitrogen doses (94, 590, 837, 1088 and 1575 kg N ha-1), five phosphorus doses (10, 72, 96, 133 and 195 kg P2O5 ha-1) and five potassium doses (75, 527, 752, 978 and 1429 kg K2O ha-1), were combined according to the experimental matrix Pan Puebla II, in 16 combinations and distributed in a randomized block design, with five repetitions. The plots consisted of six papaya plants and the four central plants were evaluated. The fertilizers urea, monoammonium phosphate and potassium chloride were used as NPK sources, respectively. The doses of N and K were split into 30 applications, one every two weeks. Phosphorus doses were split into two applications, the first at 75 days after transplantation (DAT) and the second one at 150 DAT. Fruit production was evaluated during eight months. The best results were obtained for NPK doses of 1088, 72 and 527 kg ha-1, respectively. Increasing N doses linearly increased the number of fruits per plant and yield, while increasing P and K doses reduced yield by a quadratic and linear model, respectively. The combination of NPK doses 590-72-75 kg ha-1 provided the best economic results with the highest rate of return for papaya production.